Targeting intracellular Leishmania (L.) infantum with nitazoxanide entrapped into phosphatidylserine-nanoliposomes: An experimental study. (1st December 2020) - Pinto, Erika Gracielle; Barbosa, Leandro R.S.; Mortara, Renato A.; Tempone, Andre Gustavo
Abstract: Leishmaniasis is a parasitic neglected tropical disease and result in a broad spectrum of clinical manifestations, ranging from a single ulceration to a progressive and fatal visceral disease. Comprising a limited and highly toxic therapeutic arsenal, new treatments are urgently needed. Targeting delivery of drugs has been a promising approach for visceral leishmaniasis (VL). Phosphatidylserine-liposomes have demonstrated superior efficacy in VL, targeting intracellular parasites in host cells through macrophage scavenger receptors. In this work, we investigated the in vitro and in vivo efficacy of the antihelminthic drug nitazoxanide in a nanoliposomal formulation against Leishmania ( L. ) infantum . Physicochemical parameters of liposomes containing nitazoxanide (NTZ-LP) were determined by dynamic light scattering and small angle X-ray scattering. The efficacy of the formulation was verified in an intracellular amastigote model and in an experimental hamster model. Our findings showed that NTZ-LP was able to eliminate the amastigotes inside the host cell with an IC50 value of 16 μM. NTZ-LP was labelled a fluorescent probe and by spectrofluorimetry, we observed that the infected macrophages internalized similar levels of the drug to the uninfected cells. The confocal microscopy images confirmed the uptake and demonstrated a diffuse distribution of the NTZ-LP in the cytoplasm of Leishmania -infected macrophages, with the vesicles in a closer proximity to the parasites. For the in vivo efficacy, the liposomal NTZ-LP was administrated intraperitoneally to Leishmania -infected hamsters for 10 consecutive days at 2 mg/kg/day. By qPCR we demonstrated a reduction of the parasite burden by 82% and 50% in the liver (p < 0.05) and spleen (p < 0.05), respectively. NTZ (non-liposomal) was administered at 100 mg/kg/day per oral (p.o.) for the same period, but demonstrated no efficacy. This liposomal formulation ensured a targeting delivery of NTZ to the intracellular parasites, resulting in an good efficacy at a low dose in animals, and it may represent a new candidate therapy for VL. Graphical abstract: Image 1 Highlights: Nanoliposomal nitazoxanide (NTZ-LP) eliminates amastigotes of Leishmania. The uptake of NTZ-LP by infected macrophages is similar to uninfected cells. NTZ-LP localizes in a closer proximity to the amastigotes inside the macrophages. NTZ-LP reduces the parasite burden by 82% (liver) and 50% (spleen) of hamsters.